REPRESENTATION OF SPANISH AND UZBEK NATIONAL-CULTURAL WORLD VIEWS IN PHRASEO-PAREMIOLOGICAL UNITS THROUGH THE CONCEPT OF "HOME" - Shakarboyevich, Nurmukhammedov Yusuf (Journal of Learning on History and Social Sciences, 2024)
Phraseology is considered a mirror of the national cultural worldview of peoples. This article is dedicated to revealing the worldview of Spanish and Uzbek peoples through a linguocognitive and linguocultural analysis of the concept of "home," represented by phraseological and paremiological units. The obtained results are significant for research aimed at studying the processes of conceptualization and categorization of concepts in language, as well as the national and cultural aspects of linguistic signs.